Respostas bioquímicas em carpas (Cyprinus carpio) expostas ao fungicida tebuconazole (folicur® 200 ec) - Toni, Cândida (2010)
The intensive use and/or inadequate management of pesticides have led to contamination of the aquatic ecosystem, reaching the biota living there, including the fish. Pesticides can affect toxicological parameters these animals, harming their survival. In this way, the aim this study has to evaluate biochemistry changes in carps (Cyprinus carpio) after exposure to a commercial formulation of the fungicide tebuconazole (Folicur®). At first, we performed a test of acute toxicity to determine the LC50 (96h) of tebuconazole for C. carpio. The animals were exposed to concentrations 1.0, 1.5, 2.0, 2.5 and 3.0 mg/L for 96 hours. After this period, were anesthetized and euthanized. Using the whole-body method, we investigated the levels of TBARS, protein carbonyls, activities of enzymes GST, CAT, SOD and AChE, levels of non-enzymatic antioxidants GSH and AsA and metabolic parameters, among which, lactate, glycogen, glucose, ammonia, amino acids and protein. Secondly, fish were exposed to the fungicide during seven days, both in field conditions (rice paddy field) as a laboratory. The concentrations used in the laboratory (33.5 and 36.2 mg/L) were close to the concentration used for rice farming (31.9 mg/L). After the experimental periods, we sampled brain, liver and muscle of fish. The biochemical parameters analyzed were as follows: TBARS levels in brain, liver and muscle, protein carbonyl in liver, enzyme activities CAT and GST in liver and AChE in brain and muscle. In the first experiment was obtained as LC50 (96h) of tebuconazole for C. carpio concentration 2.37 mg/L. The body levels of TBARS showed to be high at all concentrations tested. In contrast, the enzymes GST, CAT and SOD showed reduction in their activities. The levels of GSH and AsA were also decreased after the same period. Regarding the activity of AChE and the levels of protein carbonyls, there were no statistically significant changes. Among the metabolic parameters, there was an increase in the levels of glycogen and glucose concentration 1.5 mg/L, whereas protein levels were reduced at concentrations 2.0 and 2.5 mg/L. In the second experiment, we observed increased levels of TBARS in brain only in the field condition, while in liver and muscle this increase was observed both in field and laboratory. Likewise, the levels of protein carbonyls increased in both experimental conditions. The activity of AChE in brain was increased only in the field condition, whereas in the laboratory no significant change was observed. The activities of CAT, GST and AChE in muscle showed no significant change in both experimental conditions. The results of this research, considering the two experiments show that this fungicide causes disorders in antioxidants and metabolic parameters in fish exposed, indicating the occurrence of oxidative stress, which can compromise their survival in the wild. The evaluation of TBARS levels and protein carbonyl in the liver of carp can be used as a biomarker of exposure to tebuconazole.